OPTIMALISASI ELECTRONIC WORD OF MOUTH DAN CITRA MEREK UNTUK MENINGKATKAN KEPUTUSAN PEMBELIAN PADA UMKM SEAFOOD 25 RESTORAN DUMAI - Nasrullah Nasrullah; Tiara Yuriska; Rr Meiyaqi Cesya Navazka (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the influence of electronic word of mouth (e-WOM) and brand image on consumer purchasing decisions at Seafood 25 Restaurant Dumai. A quantitative approach with an explanatory research design was applied to 100 respondents selected through the Slovin formula using purposive and accidental sampling. Data were collected via a five-point Likert scale questionnaire and analyzed using multiple linear regression. Results show that: (1) e-WOM has a positive and significant partial effect on purchasing decisions (β = 0.213; sig = 0.048); (2) brand image has a positive and significant partial effect on purchasing decisions (β = 0.368; sig = 0.005); and (3) simultaneously, both variables significantly influence purchasing decisions (F = 6.979; sig = 0.001) contributing 10.8%. These findings confirm the strategic importance of proactive e-WOM management and brand image strengthening for seafood culinary SMEs.